PENGARUH PAJAK HIBURAN, PAJAK RESTORAN, DAN PAJAK REKLAME TERHADAP KINERJA KEUANGAN PEMERINTAH DAERAH PROVINSI DKI JAKARTA - Yuda Saputra (PT Sanagi Edu Konsultan, 2025)
The purpose of this research is to determine the effect of entertainment tax, restaurant tax, and advertisement tax on the financial performance of local government of DKI Jakarta Province. The research period used was 4 years, 2016-2019. The study population includes the local revenue of DKI Jakarta Province for the period 2016-2019. The sampling technique used nonprobability sampling with a saturated sampling method. The type of data used is secondary data obtained from Badan Pajak dan Retribusi Daerah (BPRD) of DKI Jakarta Province. The data analysis method used is multiple linear regression analysis. The results showed that entertainment tax has a positive effect, restaurant tax has a negative effect, advertisement tax has no effect, and entertainment tax, restaurant tax, and advertisement tax together have a positive effect on the financial performance of the regional government of DKI Jakarta Province.